2016
DOI: 10.1111/cmi.12603
|View full text |Cite
|
Sign up to set email alerts
|

A new nucleocytoplasmic RhoGAP protein contributes to control the pathogenicity ofEntamoeba histolyticaby regulating EhRacC and EhRacD activity

Abstract: Small GTPases are signalling molecules that regulate important cellular processes. GTPases are deactivated by GTPase-activating proteins (GAPs). While human GAPs have been intensively studied, no GAP has yet been characterized in Entamoeba histolytica. In this study, we identified and characterized a novel nucleocytoplasmic RhoGAP in E. histolytica termed EhRhoGAPnc. In silico analyses of the domain structure revealed a previously undescribed peptide region within the carboxy-terminal region of EhRhoGAPnc capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, E. histolytica expresses (or encodes) more than 19 Rho domain containing GTPases as compared to 18 found in human (Bharadwaj, Arya, Shahid mansuri, Bhattacharya, & Bhattacharya, 2017a;Bosch, Wittchen, Qiu, Burridge, & Siderovski, 2011). There are also few studies on the role of Rho regulatory molecules, GEF, GAP, and GDI in regulation of amoebic pathogenesis (Aguilar-Rojas et al, 2005;Bosch et al, 2011;Hernandez-Flores et al, 2016). It has been shown that the human Rac1 homologue, EhRacG, regulates cytokinesis and uroid formation, and overexpression of EhRacA affects phagocytosis but not pinocytosis in E. histolytica (Ghosh & Samuelson, 1997;Guillen, Boquet, & Sansonetti, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, E. histolytica expresses (or encodes) more than 19 Rho domain containing GTPases as compared to 18 found in human (Bharadwaj, Arya, Shahid mansuri, Bhattacharya, & Bhattacharya, 2017a;Bosch, Wittchen, Qiu, Burridge, & Siderovski, 2011). There are also few studies on the role of Rho regulatory molecules, GEF, GAP, and GDI in regulation of amoebic pathogenesis (Aguilar-Rojas et al, 2005;Bosch et al, 2011;Hernandez-Flores et al, 2016). It has been shown that the human Rac1 homologue, EhRacG, regulates cytokinesis and uroid formation, and overexpression of EhRacA affects phagocytosis but not pinocytosis in E. histolytica (Ghosh & Samuelson, 1997;Guillen, Boquet, & Sansonetti, 1998).…”
mentioning
confidence: 99%
“…It has been shown that the human Rac1 homologue, EhRacG, regulates cytokinesis and uroid formation, and overexpression of EhRacA affects phagocytosis but not pinocytosis in E. histolytica (Ghosh & Samuelson, 1997;Guillen, Boquet, & Sansonetti, 1998). There are also few studies on the role of Rho regulatory molecules, GEF, GAP, and GDI in regulation of amoebic pathogenesis (Aguilar-Rojas et al, 2005;Bosch et al, 2011;Hernandez-Flores et al, 2016).…”
mentioning
confidence: 99%
“…6 ) reinforces the hypothesis that nuclear transport mediated by the canonical nuclear protein import pathway is present from an early stage of eukaryotic evolution, as observed in phylogenetic analyses of Importin α conservation and Importin β in yeast and mammalian species members of the supergroup Opisthokonta [ 28 , 49 , 55 ]. The fact that we identified the EhCAS Exportin (CCR1), Ran, RanBP1, RandGAP, RanGEF, and NTF2 annotated in the E. histolytica genome indicates that the nuclear protein export process is present being supported by the fact that the protein EhNCABP166 contains a functional NES rich in Leucines and the Ehp53 protein that has anNES of the same type and EhRhoGAPnc as well [ 33 , 35 , 37 ] however they need to be tested experimentally. The function of the paralogous nucleotide exchange factors RhoGEF and RanGEF is to stimulate the exchange of GDP to GTP on a signaling GTPase.…”
Section: Discussionmentioning
confidence: 99%
“…2 F). Also, a computer-predicted MNLS of 5 amino acid residues towards its carboxyl terminus has been reported for the GTP exchange factor regulatory protein RanGEF called EhRhoGAPnc [ 37 ]. In contrast, at its amino terminus, it contains an NES ( Fig.…”
Section: Introductionmentioning
confidence: 99%